2008
DOI: 10.1021/jf802808h
|View full text |Cite
|
Sign up to set email alerts
|

Fractionation of Aluminum in Commercial Green and Roasted Yerba Mate Samples (Ilex paraguariensis St. Hil.) and in Their Infusions

Abstract: Different trademarks of green mate and mate tea ( Ilex paraguariensis St. Hil.) were employed in this work, the aim of which was to compare the fractionation of Al from green mate and mate tea (roasted mate) and from their infusions. Using the flame atomic absorption spectrometry technique, contents determined for Al leached to green mate and mate tea infusions varied from 12.8 to 18.1% and from 5.9 to 10.6%, respectively. The concentrations of phenolics in infusions were determined using the Folin-Ciocalteu m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
12
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 25 publications
2
12
0
Order By: Relevance
“…The only data available on this subject in Brazil are the studies carried out in the State of Paraná and in the neighboring State of Rio Grande do Sul, Brazil, where aluminum content was determined in infusions of roasted yerba mate samples. According to these authors, Al concentration in Parana varied from 0.5 to 1.67 mg/L [17,19], which is exactly the same value as determined in the present work. However, in Rio Grande do Sul, aluminum content in the infusions was incredibly high, e.g., 445 mg/L.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The only data available on this subject in Brazil are the studies carried out in the State of Paraná and in the neighboring State of Rio Grande do Sul, Brazil, where aluminum content was determined in infusions of roasted yerba mate samples. According to these authors, Al concentration in Parana varied from 0.5 to 1.67 mg/L [17,19], which is exactly the same value as determined in the present work. However, in Rio Grande do Sul, aluminum content in the infusions was incredibly high, e.g., 445 mg/L.…”
Section: Resultssupporting
confidence: 88%
“…As to mineral composition, several studies have been carried out to determine the content of bioactive metals in I. paraguariensis and its infusions [17][18][19], including a vast review on the matter [2]. These metals can be either toxic like lead or benefic like zinc.…”
mentioning
confidence: 99%
“…For most elements, the extraction is in the range of 20-60%. In previous studies carried out by other authors, it was found that Al extraction was 10.6% (Gomes daCosta et al 2009), while that of Fe,Mg, K, Ca, Mn, Zn, and Cu was 12.7, 37.6, 58.7, 13.4, 38.2, 42.4, and 90.2%, respectively (Tenorio Sanz & Torija Isasa …”
mentioning
confidence: 86%
“…Polyphenols present in yerba mate can complex with Al. Gomes da Costa et al (2009) observed that Al concentration in the extract increased with decreasing polyphenol concentration. Thus, the low extraction of Al observed in the present work can be related to the high concentration of polyphenols present in the analysed yerba mate, where Al is bound to polyphenols.…”
Section: Extraction By Hot Watermentioning
confidence: 97%
See 1 more Smart Citation